Divided we Stand: Cities, Social Unity and Post-War Reconstruction in Soviet Russia, 1945–1953. (16th October 2015) - DALE, ROBERT
Abstract: This article explores the divisions created by the Great Patriotic War, its aftermath and the reconstruction of Russian cities in the late 1940s and early 1950s. It examines the conflicts created by rebuilding housing, infrastructure, restoring communities and allocating resources in cities where war's painful legacy continued to be felt. The war's impact varied enormously between cities on the frontlines and in the rear. Contrary to official propaganda rebuilding was a protracted process, which created divisions rather than unity.